2008
DOI: 10.1002/ibd.20420
|View full text |Cite
|
Sign up to set email alerts
|

Resistin-like molecule β regulates intestinal mucous secretion and curtails TNBS-induced colitis in mice

Abstract: A direct participation in maintaining the mucosal defense barrier can be ascribed to RELMbeta in line with a regulatory role in intestinal inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
72
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(76 citation statements)
references
References 54 publications
4
72
0
Order By: Relevance
“…3C). This notion is supported by the recently reported observation that fetal calf serum induces the expression of RELM␤ in vitro (25). Although inhibition of the IGF-I receptor (IGFR) significantly reduced RELM␤ expression, a slightly more significant reduction was observed when both EGFR and IGFR were inhibited simultaneously.…”
Section: Pharmacological Inhibition Of Akt and Growth Factor Signalinmentioning
confidence: 53%
“…3C). This notion is supported by the recently reported observation that fetal calf serum induces the expression of RELM␤ in vitro (25). Although inhibition of the IGF-I receptor (IGFR) significantly reduced RELM␤ expression, a slightly more significant reduction was observed when both EGFR and IGFR were inhibited simultaneously.…”
Section: Pharmacological Inhibition Of Akt and Growth Factor Signalinmentioning
confidence: 53%
“…It has been previously shown that recombinant RELM-␤ can evoke a significant increase in MUC2 gene expression in HT29-C1.16E cells, as well as an increase in Muc2 secretion by murine intestinal goblet cells (28). In the same study, pretreatment of mice with RELM-␤ was shown to significantly attenuate trinitrobenzene sulfonic acid (TNBS)-induced colitis (28). Another goblet cell marker, TFF-3, has been shown to protect epithelial cells by contributing in mucosal defense (3).…”
mentioning
confidence: 97%
“…The importance of the Muc2 mucin in organizing the colon mucus protection is further strengthen by the report that two mouse strains with diarrhea and colon inflammation were shown to have two separate spontaneous mutations in the Muc2 mucin (Heazlewood et al 2008). Importantly, the production of mucin is regulated by protein kinases, for example, resistin and resistin-like molecule (RELM) beta upregulated mucin expression which dependent on the kinase activities of protein kinase C (PKC), tyrosine kinases, and extracellular-regulated protein kinase (Krimi et al, 2008); Cathelicidin stimulates colonic mucus synthesis by up-regulating MUC1 and MUC2 expression through a mitogen-activated protein kinase pathway (Tai et al, 2008).…”
Section: Mucus Layermentioning
confidence: 86%